Exploiting Bi-Directional Self-Organizing Tendencies in Team Sports: The Role of the Game Model and Tactical Principles of Play - Ribeiro, João; Davids, Keith; Araújo, Duarte; Guilherme, José; Silva, Pedro; Garganta, Júlio (Frontiers in Psychology, 2019)
Research has revealed how inherent self-organising tendencies in athletes and sports teams can be exploited to facilitate emergence of dynamical patterns in synergy for-mation in sports teams. Here we discuss how game models, and associated tactical prin-ciples of play, may be implemented to constrain co-existing global-to-local and local-to-global self-organisation tendencies in team sports players during training and perfor-mance. Understanding how to harness the continuous interplay between these co-existing, bi-directional, coordination tendencies is key to shaping system behaviours in sports training. Training programs are traditionally dominated by designs, which shape the self-organising tendencies of players and teams at a global-to-local scale by coaches imposing a tactical/strategical plan with associated tactical principles of play. Neverthe-less, recent research suggests that performers also need to be provided with opportuni-ties to explore self-organising tendencies that emerge at the local-to-global scale in train-ing. This directional tendency in synergy formation can be facilitated by players being given opportunities to actively explore different adaptive and innovative performance solutions, coherent with principles of play circumscribed in an over-arching game model. Developing methods (coaching sessions rooted on principles of dynamical systems theo-ry that foment the development of such local-to-global relations) to exploit the continu-ous interplay between these co-existing tendencies within sports teams may promote more effective and efficient athlete skill training programs, in addition to enhancing performance.